CXCR2 May Serve as a Useful Index of Disease Activity in Interstitial Lung Disease Associated With Primary Sjögren’s Syndrome - Zhu, Xiaofang; Lu, Saisai; Zhu, Lixia; Yu, Mengjiao; Wei, Tingting; Zhu, Xiaochun; Chen, Dan; Chen, Chengshui (Frontiers in Molecular Biosciences, 2021)
Primary Sjögren’s Syndrome (pSS) is a chronic systemic autoimmune disease characterized by typical autoantibody production and lymphocytic-mediated exocrine gland damage. Interstitial lung disease (ILD) is a common complication of pSS, which might lead to a poor prognosis in pSS. However, the pathogenesis of ILD in pSS is still unclear. In this study, we investigated the gene expression profiles of minor salivary gland (MSG) from 36 ILD-pSS patients and 128 non-ILD-pSS patients by RNA-sequencing (RNA-seq). In the remarkably enriched chemokine-mediated signaling pathway, C-X-C Motif Chemokine Receptor 2 (CXCR2), a receptor for interleukin 8 (IL-8), which participates in the activation of neutrophils, has been found to elevate both in MSG and plasma from pSS patients with ILD compared with those without ILD (p <0.001). Furthermore, the CXCR2 expression level in MSG and plasma were significantly associated with diffusing capacity of the lungs for carbon monoxide (DLCO), erythrocyte sedimentation rate (ESR), and EULAR Sjögren’s syndrome disease activity index (ESSDAI) in pSS with ILD. Therefore, with its potential role in the progression of ILD in pSS patients and its strong association with their clinical manifestations, CXCR2 may serve as an useful index for disease activity in interstitial lung disease associated with Sjögren's syndrome for better clinical practice.